Assessment of the effectiveness of tax amnesties as a mechanism for strengthening state institutional resilience in times of crisis - Sydorovych, Olena; Bukovskyi, Mykola (Herald of Economics, 2025)
The article examines the role of tax amnesties as a tool for strengthening the institutional capacity of the state under conditions of socio-economic crises and hybrid threats. It analyzes the contradictory aspects of applying amnesties in foreign and domestic tax practices. Criteria for the effectiveness of tax amnesties are proposed, which consider not only fiscal results but also the impact on institutional trust and the long-term stability of the tax system.Introduction. During periods of deep socio-economic crises and in the context of countering hybrid threats, the institutional capacity of the state becomes a decisive factor for its resilience. Tax institutions are the cornerstone of the state’s existence, as they ensure its fiscal sovereignty, citizens’ trust in a fair tax system, and the legitimacy of social institutions. Modern challenges necessitate the search for non-traditional stabilization tools, among which tax amnesties hold a special place.The purpose of the article is a comprehensive assessment of the effectiveness of tax amnesties as a tool for strengthening the state’s institutional capacity in times of crisis. This is achieved by analyzing their impact on the level of tax discipline, trust in state institutions, and the long-term stability of the budgetary system, followed by the formulation of practical recommendations for optimizing amnesty mechanisms to achieve institutional resilience.Results. The conceptual essence of tax amnesties has been identified. The structural features of implementing tax reforms in foreign practice have been outlined. The historical experience of conducting tax amnesties in Ukraine (2005, 2011, 2015, 2021-2023) has been analyzed. It has been substantiated that to achieve an institutional effect, tax amnesties must be part of a comprehensive reform program and not viewed as an isolated measure.Conclusions and Prospects for Further Research. Tax amnesties can become an effective tool for strengthening institutional capacity only if they are integrated into the overall strategy of tax reform. A key success factor is building citizens’ trust in the state through guarantees of security, transparency, and further support for legalized businesses. The effectiveness of amnesties should be assessed not only by fiscal indicators but also by their impact on institutional trust and the long-term stability of the tax system. Under hybrid threats, tax amnesties can help reduce the economy’s vulnerability through de-shadowing and strengthening fiscal sovereignty.